PENGARUH STRUKTUR KEPEMILIKAN, LEVERAGE DAN RETURN ON ASSETS (ROA) TERHADAP KEBIJAKAN DIVIDEN (Studi Empiris pada Perusahaan Nonkeuangan yang Terdaftar di Bursa Efek Indonesia) - Noor Rachmad, Anggie; Muid, Dul (Diponegoro Journal of Accounting, 2013)
This study aims to analyze the effect of ownership structure, Leverage, and Return On Assets on dividend policy of all non-financial companies listed st the Indonesia Stock Exchange in the year 2009-2011. This research is an empirical study with purposive sampling techniques in data collection. Data are obtained from secondary annual report of 33data non-financial companies listed at the Stock Exchange in the year 2009-2011. Data are analyzed using multiple regression. Hypothesis testing results indicate that managerial ownership, Leverage, and Return On Assets as well as control variable firm size significantly affect dividend policy. Furthermore, institutional ownership and minority ownership do not significantly influence the dividend policy.